Investigating Protein–Ligand Interactions by Solution Nuclear Magnetic Resonance Spectroscopy. Issue 8 (11th April 2018) - Becker, Walter; Bhattiprolu, Krishna Chaitanya; Gubensäk, Nina; Zangger, Klaus
Abstract: The front cover artwork is provided by the group of Prof. Klaus Zangger at the University of Graz. The image shows the combination of protein‐based and ligand‐based methods in order to study protein–ligand interactions by solution NMR spectroscopy. Read the full text of the Review at 10.1002/cphc.201701253 . Abstract : "Here we present an overview of solution NMR methods to investigate protein‐ligand interactions. The information provided ranges from the presence of binding to the complete structure of the complex …" This and more about the story behind the front cover can be found in the Review at10.1002/cphc.201701253 .